Keyboards in contemporary praise and worship - Kerr, Ed (Vocalist); Kerrtunes (Firm) ([Lindale, TX] : Kerrtunes, 2005)
"Topics include: building triads and 7th chords, modulations, voices and voice leading, inversions, creating melodic motion, complementing guitars, layering sounds, and reharmonizing"--Container.
DVD.
Instructional video.
Includes a downloadable companion booklet.
Bonus features require Adobe Acrobat Reader.
Bonus features include hymn arrangements in pdf [portable document file] format.
Ed Kerr, narrator and piano ; Paul Baloche, acoustic guitar ; Bill Scott, bass.
Keywords: Keyboard instrument music -- Instruction and study